Book Review - Levatino, Antonina (Migration Letters, 2014)
Martin Geiger & Antoine Pécoud (eds.), Disciplining the Transnational Mobility of People, Palgrave Macmillan, 2013, 271 pp., (ISBN 978-1-137-26306-3). In the last decades a very diverse range of initiatives have been undertaken in order to intensify and diversify the ways human mobility is managed and restricted. This trend towards a ‘diversification’ of the migration control strategies stems from the increased awareness by the nation-states of the profoundly controversial nature of the migration management enterprise because of its political, economic, social and moral implications.